2020
DOI: 10.3390/ijerph17145221
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Negotiations for Improving Research Environment and Burnout among Young Physician Researchers in Japan

Abstract: Physician scientists in Japan are often too busy to be sufficiently involved in research work. This cross-sectional study aimed to investigate their experiences negotiating with their superiors to improve their research environment and determine its relationship with psychological burnout. Among 1790 physician awardees of Grants-in-Aid for Young Scientists in 2014–2015, 490 responded (response rate 27.4%) and 408 were eligible for analysis. Outcome measures included two negotiation experiences: for reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…With respect to the significant association between private university hospitals and spending ≥80 h/week at the hospital, previous studies have noted that doctors working at such hospitals in Japan are required to fulfill three different roles (medical care, research, and teaching) and that this normalizes overwork. [18][19][20] In some hospitals, salaries are also low, and doctors have to take on additional part-time work to make ends meet. When promoting the reform of doctors' working practices, further support measures to guarantee the salaries of doctors employed in university hospitals should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the significant association between private university hospitals and spending ≥80 h/week at the hospital, previous studies have noted that doctors working at such hospitals in Japan are required to fulfill three different roles (medical care, research, and teaching) and that this normalizes overwork. [18][19][20] In some hospitals, salaries are also low, and doctors have to take on additional part-time work to make ends meet. When promoting the reform of doctors' working practices, further support measures to guarantee the salaries of doctors employed in university hospitals should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Japan, on the other hand, does not appear to have an environment that encourages its clinician researchers to continue with basic research. Even for those who secure independent funding, the demands of clinical work cause a high attrition rate (Toyoshima et al, 2020). This situation is also a concern at our institute: an internal survey found that 48% of our Ph.D. graduates go on to work in hospitals, most likely as clinicians.…”
Section: Industry Jobs Discourage Migrationmentioning
confidence: 99%
“…Indeed, the fourth Medium-Term Plans of National University Corporations, which are required by law to establish Key Performance Indicators to achieve the ministry’s Medium-Term Goals, state that they will measure their performance with a focus on quantitative indicators, including the number of published articles 8. This is true in the field of medicine; combined with the fierce competition for positions as medical researchers, publishing in journals with high IFs is encouraged regardless of differences in fields 9. Consequently, this merit-based evaluation, combined with an overcompetitive environment, puts pressure on researchers to publish, potentially making them more susceptible to research misconduct 10–12…”
Section: Introductionmentioning
confidence: 99%
“… 8 This is true in the field of medicine; combined with the fierce competition for positions as medical researchers, publishing in journals with high IFs is encouraged regardless of differences in fields. 9 Consequently, this merit-based evaluation, combined with an overcompetitive environment, puts pressure on researchers to publish, potentially making them more susceptible to research misconduct. 10–12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation